BEHAVIOR OF BREAST SELF EXAMINATION (BBS) ON FEMALE STUDENTS IN SMA NEGERI 6 PEKANBARU YEARS 2016 - Maharani, Riri; Fransisca, Lisa (Fakultas MIPA dan Kesehatan Universitas Muhammadiyah Riau, 2017)
Breast Self Examination (BSE) is an examination technique where one woman check her own breasts with a look and feel with a finger to detect whether or not there is a lump in her breast ( Djawarut , 2014). BSE is one way to detect breast cancer early . According Sutjipto , at this time have been found with breast cancer at a young age . This study aims to determine the behavior of adolescent girls in SMA 6 Pekanbaru 2016 . This type of research is a quantitative analytical research. With design cross- sectional. The sample was SMA Negeri 6 Pekanbaru class X and XI which totaled 129 with a population of 371 people. The sampling technique used is stratified random sampling. The analysis used were univariate and bivariate with Chi Square test. Based on the results of the study showed most respondents did conduct BSE in 2 (1.6 %), respondents with low knowledge, 104 (100 %), respondents with negative attitudes were 107 (100 %), respondents were not doing as much as 110 (100 %), respondents who never get as much information as much as 105 (100 %), and respondents who have no family support as many as 106 (100 %), Based on the statistical test P value obtained from five variables < Î± (0.05), there is a significant relationship between knowledge, attitudes, actions, mass media and family support to conduct breast self-examination. Advice can be given is the school invited health authorities to work together to educate the student through counseling in an effort to improve reproductive health so that students know the importance of early behavioral measures BSE.